Analisis Hukum Keluarga Islam Terhadap Tradisi Abekhalan Dan Implikasinya Pada Calon Pengantin - Taufik (ASA, 2021)
Abhekalan tradition is a tradition of East Java, especially Bondowoso. In practice, the tradition gets a lot of spotlight because it has violated the rules of Islam so that it deviates from the sacred purpose of the marriage sermon. A bhekalan in the tradition of Islamic law is synonymous with khitbah (proposal). The purpose of the courtship is to show the seriousness of a person to establish a relationship and bind the woman who has been betrothed so as not to be betrothed by another man, as long as the first suitor has not canceled the proposal.The purpose of this research is to reveal the phenomenon of the people of Sukokerto, Pujer District in carrying out the Abhekalan tradition and its implications for the bride and groom who will enter the wedding gate.This study uses a descriptive qualitative approach. With this type of Empirical Law research. The data source uses primary and secondary data sources. The data collection techniques are observation, interviews and documentation. The data analysis uses the Miles - Huberman and Saldana Interactive Analysis Model which includes data condensation, data reeduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation of data sources, methods, and theoriesThe results showed that there was a deviant behavior due to the Abhekalan Tradition that occurred in the village of Sukokerto, Pujer District, Bondowoso regency, as well as the analysis of Islamic family law perspective. The tradition of "Abhekalan," as a pre-marriage process is a hereditary tradition in most East Javanese communities, especially Bondowoso, including Pujer District .. In the analysis of Islamic family law, this phenomenon can not be claimed as a right. There are various verses of the Qur'an and Hadith that can be used as an analysis knife